2019
DOI: 10.1155/2019/7685359
|View full text |Cite
|
Sign up to set email alerts
|

A New Two‐Dimensional Mutual Coupled Logistic Map and Its Application for Pseudorandom Number Generator

Abstract: Given that the sequences generated by logistic map are unsecure with a number of weaknesses, including its relatively small key space, uneven distribution, and vulnerability to attack by phase space reconstruction, this paper proposes a new two-dimensional mutual coupled logistic map, which can overcome these weaknesses. Our two-dimensional chaotic map model is simpler than the recently proposed three-dimensional coupled logistic map, whereas the sequence generated by our system is more complex. Furthermore, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…Pseudorandom bit sequence (PRBS) plays an important role in many fields, such as spread spectrum communication, numerical simulation, and cryptography [7,8]. Recently, chaotic systems are regarded as effective nonlinear sources in generating PRBS for their wonderful properties, including sensitivity on initial conditions and parameters, ergodicity, long-term unpredictability, and pseudorandomness [9][10][11]. Overall, the one-dimensional chaotic map is the most widely used chaotic system for designing PRBG.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudorandom bit sequence (PRBS) plays an important role in many fields, such as spread spectrum communication, numerical simulation, and cryptography [7,8]. Recently, chaotic systems are regarded as effective nonlinear sources in generating PRBS for their wonderful properties, including sensitivity on initial conditions and parameters, ergodicity, long-term unpredictability, and pseudorandomness [9][10][11]. Overall, the one-dimensional chaotic map is the most widely used chaotic system for designing PRBG.…”
Section: Introductionmentioning
confidence: 99%
“…The means of the P values of each test are illustrated in Table 3. As the table shows, there is a significant difference between the two groups: the first group results being calculated based on the current study, whilst the second group pertains to the reference outcomes [31]. Additionally, according to the results illustrated in Table 2, the bit sequence of this research has passed all the tests successfully.…”
Section: Nist Statistical Testsmentioning
confidence: 84%
“…Therefore, for the current study, it has been found that the sequence delivers good statistical performance and can achieve true randomness. In Table 3, a comparison with the reference outcomes [31] is provided. Clearly, the results of the current study demonstrate better means of the P_values than the same test results obtained from the reference [31].…”
Section: Nist Statistical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classical chaotic maps (logistic and henon) are faster because they have a lower number of computational operations. PRNGs based on the new chaotic maps outperform some of the existing chaos-based PRNGs [21], [38] but are slower than the PRNGs proposed in [15], [50], [51]. The lower efficiency is because the proposed generators were designed to produce only 8 bits per iteration, rather than multiple bytes.…”
Section: G Speed Analysismentioning
confidence: 95%